Leadership Literacy in the Digital Era : A Study of Teacher and Student Understanding - Iskandar, Rossi; Setiawan, Rudi; Maksum, Arifin; Nisphia, Jasmin; Amelia, Winda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to analyze the understanding of technology-based leadership literacy in elementary schools. The research used a descriptive method with a qualitative approach, involving elementary school teachers and students in West Jawa as subjects. Primary data was gathered through interviews, observations, surveys, and documentation, while secondary data was sourced from previous studies by other researchers. Nvivo12 software was utilized for data analysis. The research findings revealed that literacy in the digital era is very important to teach students from an early age to build superior student character. Literacy skills in the digital era will encourage students to have competence in solving problems, broad insight, and be critical and creative in carrying out their activities.